2013
DOI: 10.1080/07399332.2012.736577
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Experiences of Western Australian Women Attending a Specialist Childbirth and Mental Illness Antenatal Clinic

Abstract: Our purpose was to explore the pregnancy experiences of Australian women attending a specialized childbirth and mental illness (CAMI) antenatal clinic. A qualitative exploratory design was selected to give voice to women with severe mental illness receiving antenatal care. Telephone interviews with 41 women, 24 primiparous and 17 multiparous, were analyzed using thematic analysis. Three themes emerged: "building relationships," "acknowledging me as a person with special needs," and "respecting and understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…Perinatal mental health problems have a significant impact on women, children, and families (Hauck et al, 2013). Research in the UK identified that, potentially, the most modifiable determinant for improved child outcomes is maternal health, particularly depression.…”
mentioning
confidence: 99%
“…Perinatal mental health problems have a significant impact on women, children, and families (Hauck et al, 2013). Research in the UK identified that, potentially, the most modifiable determinant for improved child outcomes is maternal health, particularly depression.…”
mentioning
confidence: 99%
“…Findings of an exploratory qualitative study by Hauck et al. () of 41 women with severe mental health illness attending a specialist childbirth and mental health antenatal clinic in Australia concluded that having access to a multidisciplinary team contributed to women's feelings of support and feelings of well‐being. This echoes recommendations by the Irish Department of Health () with the recent publication of the first National Maternity Strategy 2016–2026 , for collaboration between midwives and mental health services, perinatal psychiatrist, and mental health, to ensure appropriate and timely support for women with PMH issues and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women with pre‐existing mental health (MH) disorders should at least undergo risk assessment at the first booking visit and, in the absence of a specialist PMH service, be afforded priority when referred onwards to local Mental Health services (MDE ). Women with PMH needs derive significant benefits from collaboration between specialist mental health services and continuity of care during pregnancy (Hauck et al., , MBRRACE‐UK, ).…”
Section: Background and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women need to share their story in the context of a safe relationship where professionalism and continuity are prominent . Research shows that providing support and individualised care means building relations and this promotes both physical and mental health in pregnant women .…”
Section: Introductionmentioning
confidence: 99%